Effect of sonication on the structural, optical and photocatalytic characteristics of ZnO nanostructures - U. K. Panigrahi; D. Das; Shamima Hussain; J. Giri; A. K. Panda; P. K. Satapathy; P. Mallick (Discover Materials)
Abstract The removal of organic dyes from wastewater is a demanding environmental concern. This study explores the photocatalytic efficiency of ZnO in degrading methylene blue under light irradiation. ZnO nanoparticles were synthesized via ultrasound assisted wet chemical route. Structural characterization of the samples revealed the crystallization of cubic zinc blende phase in the background of wurtzite phase of ZnO. Influence of ultrasonic irradiation time is realized by declining size of the crystallite along with declining trend of the band gap energy E g . In addition, the fraction of cubic phase is increased along with the shape transformation from spherical to rod shape morphology of ZnO nanostructures with increasing sonication time. Presence of more structural defect concentration as envisioned from Raman study would account for the better catalytic activity of the sample prepared through twenty minutes of sonicated assistantship. Photoluminescence study reveals that presence of various defects in our samples. The ZnO sample synthesized with 20 min of sonication exhibited an apparent rate constant of ~ 0.0354 min−1 for the catalyst towards methylene blue (cationic dye) degradation at optimum condition of pH 12 and time 40 min with the loading of 0.02 g catalyst per 0.1 L of the dye solution. The optimum % of degradation of ~ 74.69% of dye degradation was achieved by our target sample. Our study thus provides an opportunity to utilize the material for environmental remediation and blue LED applications.